Using dispersion modeling for ground level concentration - ESSA, KHALEDS.M.; MUBARAK, FAWZIA (MAUSAM, 2011)
A short range model calculating ground-level concentration from elevated sources is estimated, which realized a Fickian-type formula. Taking the source and mixing height are functions of the wind velocity and eddy diffusivity profiles. The model estimated with an exact solution of the advection diffusion equation is compared with experimental ground level concentrations using meteorological data collected near the ground.